Is There A Correlation Between the Coping Strategy Used and the Quality of Life of the Caregivers of Schizophrenic Patients in a Family Unit - Nihayati, Hanik Endang; Gunawan, Dwiko Nur; Wahyuni , Sylvia Dwi; Yunita, Fildzah Cindra (International Journal of Psychosocial Rehabilitation, 2020)
The caregiver in a family where there is a person with schizophrenia will use coping strategies to deal with the stressors related to caregiving. Based on the previous studies, differences in the use of coping strategies may produce different levels of quality of life. This study aims to reveal how the use of specific coping strategies may affect the carer’s quality of life. This study used a cross-sectional design with quantitative data. The samples consisted of 222 caregivers in a family with a person with schizophrenia. The sample was obtained using purposive sampling. The data was obtained through the Ways of Coping questionnaire and the Schizophrenia Caregiver Quality of Life Questionnaire (S-CGQoL) which were then analyzed using the Spearman Rho correlational test. The results showed that there was a significance value of 0.05 (p=0.00). The correlation coefficient of r=-0.476 indicates that there is a negative correlation and a moderate strength of the relationship found. The use of appropriate coping strategies by each caregiver in the family of a person with schizophrenia is recommended, specifically Problem-focused Coping (PFC). The use of an Emotion-Focus Coping (EFC) strategy is more effective at resolving problems over a short period. There is a significant negative correlation between coping strategies and the quality of life of the caregivers in a family where there is a person with schizophrenia. This means that the more that caregivers use EFC strategies, the lower their quality of life.